2018
DOI: 10.3390/nu10010062
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean Diet and Inflammatory Markers

Abstract: The aim was to assess inflammatory markers among adults and adolescents in relation to the adherence to the Mediterranean diet. A random sample (219 males and 379 females) of the Balearic Islands population (12–65 years) was anthropometrically measured and provided a blood sample to determine biomarkers of inflammation. Dietary habits were assessed and the adherence to the Mediterranean dietary pattern calculated. The prevalence of metabolic syndrome increased with age in both sexes. The adherence to the Medit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
141
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(159 citation statements)
references
References 68 publications
13
141
1
4
Order By: Relevance
“…In this way, several studies showed that a high-quality dietary intake, characterized using the Dietary Approaches to Stop Hypertension (DASH) index, the Healthy Eating Index (HEI), and the Mediterranean Diet Index, has high anti-inflammatory potential [9,71]. In particular, our results are in line with those found by Sudera et al [72] who, after studying 73 males and 161 females between 18 and 65 years old living on the Balearic Islands, found that low adherence to the MDP was directly associated with a worse profile of plasmatic inflammation markers. Specifically, higher adherence to the MPD was associated with higher levels of adiponectin, and lower levels of leptin, TNF-α, PAI-1, and hs-CRP in the mentioned study.…”
Section: Discussionsupporting
confidence: 92%
“…In this way, several studies showed that a high-quality dietary intake, characterized using the Dietary Approaches to Stop Hypertension (DASH) index, the Healthy Eating Index (HEI), and the Mediterranean Diet Index, has high anti-inflammatory potential [9,71]. In particular, our results are in line with those found by Sudera et al [72] who, after studying 73 males and 161 females between 18 and 65 years old living on the Balearic Islands, found that low adherence to the MDP was directly associated with a worse profile of plasmatic inflammation markers. Specifically, higher adherence to the MPD was associated with higher levels of adiponectin, and lower levels of leptin, TNF-α, PAI-1, and hs-CRP in the mentioned study.…”
Section: Discussionsupporting
confidence: 92%
“…), which have been shown to exert antioxidant and antiinflammatory effects and thereby may conceivably protect from neurodegeneration. 36,[41][42][43][44] Concomitantly, these MeDi components and the whole MeDi pattern have been associated with favorable gut microbiota characteristics, [45][46][47] possibly ameliorating the gut-tobrain signaling and therefore beneficially affecting neuronal functioning in both the enteral and central nervous system. [38][39][40]48 Nevertheless, given that the association of MeDi with lower probability score of pPD in our study still remains when performing the analysis without constipation, this raises the possibility that association of MeDi with other pPD markers may be also pertinent.…”
Section: Discussionmentioning
confidence: 99%
“…International literature emphasizes the importance of the Mediterranean dietary pattern for the prevention of CNCDs in this age group 31,32 . However, despite this scientific evidence, it should be noted that the dietary pattern of a population is the result of multiple aspects, including individual, cultural and social factors.…”
Section: Discussionmentioning
confidence: 99%
“…The economic factor makes it difficult or impossible for elderly persons to apply a healthy diet that includes the daily intake of fruits, vegetables, whole grains, oleaginous fruit, legumes, meat, milk and dairy products, as these represent a significant expenditure in comparison with other expenses and individual and family needs. The challenge is therefore to adapt the dietary pattern of the region in which the individual resides, with achievable and feasible changes to the social and health reality of each person, always seeking the best dietary arrangement combined with the pleasure that only good food provides 31,32 .…”
Section: Discussionmentioning
confidence: 99%